THE CURRENT STRESS OF EARTH'S CRUST IN THE TERRITORY OF UZBEKISTAN ACCORDING TO FOCAL EARTHQUAKE MECHANISMS - T. L. Ibragimova; R. S. Ibragimov; M. A. Mirzaev; Yu. L. Rebetsky (Геодинамика и тектонофизика, 2021)
The current stress of Earth's crust in the territory of Uzbekistan has been studied using a focal earthquake mechanisms catalogue that includes the data provided by many authors. Stress reconstructions are based on the cataclastic analysis of displacements along fractures. For reconstructing the stress state at different depths of the crust in several seismically active regions of the study area, we consider a minimum number of earthquakes in a homogeneous sample equal to 6 and an averaging radius of 10 to 30 km within a single domain. The azimuths and dip angles of the principal stress axes, Lode – Nadai coefficients, geodynamic types of stress modes, relative (normalized to rock strength) values of maximum shear stresses, and effective pressure values are determined. Maps showing the spatial distribution of the studied parameters are constructed for both the entire seismically active layer and the depth layers. Stress fields are reconstructed and compared at two hierarchical levels based on the parameters of focal mechanisms of weak and moderate earthquakes (М≤4.5) and those of strong (М≥5.0) earthquakes. "Tectonic Stresses of Eurasia", the Internet resource created by IPE RAS, is used to visualize the stress field reconstructed from the data on strong (М≥5.0) earthquakes.